Das Unwetter vom August 1983 im Kantabrischen Spanien (Baskenland, Kantabrien und atlantisches Navarra) - Molina, José Jaime Capel (ERDKUNDE, 1985)
This paper presents a synoptic presentation of the meteorological conditions which caused torrential rains with catastrophic consequences to fall in Spain between August 25th-27th,1983. They affected the Basque country, the Cantabrian zone and the Atlantic section of Navarra.